2021
DOI: 10.1186/s13195-021-00837-0
|View full text |Cite
|
Sign up to set email alerts
|

Predict Alzheimer’s disease using hippocampus MRI data: a lightweight 3D deep convolutional network model with visual and global shape representations

Abstract: Background Alzheimer’s disease (AD) is a progressive and irreversible brain disorder. Hippocampus is one of the involved regions and its atrophy is a widely used biomarker for AD diagnosis. We have recently developed DenseCNN, a lightweight 3D deep convolutional network model, for AD classification based on hippocampus magnetic resonance imaging (MRI) segments. In addition to the visual features of the hippocampus segments, the global shape representations of the hippocampus are also important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Data type AUC [51] sMRI 0.8722 [52] sMRI 0.861 [53] sMRI 0.76 [57] SNPs (482) 0.842 [16] SNPs (2500) 0.719 [58] SNPs (11) 0.8949 MRI 0.993 [59] sMRI 0.9252 [60] amyloid PET 0.908 [61] amyloid PET + MRI 0.9234 [63] SNPs (200) 0.62 [17] SNPs (20 & 50) 0.68 [18] SNPs (41) 0.6807 [19] SNPs (20) 0.689 *Note: images data results were measured by ACC journal.ump.edu.my/ijsecs ◄ Furthermore, when the results of ML and DL based approaches were compared in terms of genetic variants data and neuroimaging data, shown Table 3, it was found that DL based approaches had achieved better performance in Neuroimaging data compared to ML based approaches, while they were relatively poor with SNPs data.…”
Section: Table 1 ML Approaches Results With Mri and Snps Data Ref Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Data type AUC [51] sMRI 0.8722 [52] sMRI 0.861 [53] sMRI 0.76 [57] SNPs (482) 0.842 [16] SNPs (2500) 0.719 [58] SNPs (11) 0.8949 MRI 0.993 [59] sMRI 0.9252 [60] amyloid PET 0.908 [61] amyloid PET + MRI 0.9234 [63] SNPs (200) 0.62 [17] SNPs (20 & 50) 0.68 [18] SNPs (41) 0.6807 [19] SNPs (20) 0.689 *Note: images data results were measured by ACC journal.ump.edu.my/ijsecs ◄ Furthermore, when the results of ML and DL based approaches were compared in terms of genetic variants data and neuroimaging data, shown Table 3, it was found that DL based approaches had achieved better performance in Neuroimaging data compared to ML based approaches, while they were relatively poor with SNPs data.…”
Section: Table 1 ML Approaches Results With Mri and Snps Data Ref Nomentioning
confidence: 99%
“…The model attained a testing accuracy of 99.30. Another approach exploited MRI data in [59] to predict AD. Researchers used structural MRI features extracted from the hippocampus area of 933 subjects.…”
Section: Magnetic Resonance Imaging (Mri) Datamentioning
confidence: 99%
“…amyloid PET, and the recent approval of its use by the U.S. FDA (Jie et al, 2021). Importantly, these studies, together with the literature on unsupervised learning approaches applied to AD (Gamberger et al, 2016; Gamberger et al, 2017; Martí-Juan et al, 2019; Ferreira et al, 2019; Alashwal et al, 2019; Wang et al, 2021; Katabathula et al, 2021; Prakash et al, 2021, Alexander et al, 2020; Alexander et al, 2021; Prakash et al, 2021), have not used cluster-based class re-labelling for GNN’s classification of AD. Here, we have made use of the robust auto-metric GNN model by Song et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Complementing the supervised learning of GNN, unsupervised learning such as dimensional reduction, clustering and data visualisation have been used for providing further insights into heterogeneous AD data (e.g. Alashwal et al, 2019; Wang et al, 2021; Katabathula et al, 2021). In particular, some studies using clustering methods had identified sub-populations that were relatively homogeneous based on clinical and biological features (Gamberger et al, 2016; Martí-Juan et al, 2019; Ferreira et al, 2019; Prakash et al, 2021, Alexander et al, 2020; Alexander et al, 2021), differing rates of cognitive decline of sub-groups of prodromal AD patients (Gamberger et al, 2017; Alexander et al, 2020; Alexander et al, 2021), and for stratifying treatments (Prakash et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning-based methods have recently gained great momentum in both image reconstruction ( 128 ) and postprocessing ( 129 , 130 ). Here, we focus on the DL application in image postprocessing with emphasis on image segmentation in a mono-modality and registration between different modalities.…”
Section: Deep Learning In Multimodal Imaging Postprocessingmentioning
confidence: 99%